Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)
Harcèlement en ligne, blagues sexistes, sous-représentation féminine, culture du silence : des humoristes n’entendent plus à rire. Elles sont « fucking tannées », « exténuées », « fâchées ». Et certaines aménagent leurs propres « safe spaces » (espaces sûrs), si de tels lieux existent.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; dénonciations en ligne; identités LGBTQIA2+; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; safe space; sororité; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite